METODE PENAFSIRAN AL-SHâFI‘î DALAM TAFSîR AL-IMâM AL-SHâFI‘î - Abdillah, M. Masykur (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
In the Abbasid period, the understanding of the Koran is still fairly freely, each reader has its own way to understand it. Freedom in understanding the Koran is ultimately impressed the wild, especially for those who do not master language of Koran. Therefore, at that time the scholars took the initiative to make the rules in the understanding of the Koran. Al-Shâfi?î began drafting rules neatly in the form of scientific discourse that ultimately became a reference for commentators to understand the Koran. With his expertise, al-Shâfi?î interprets the verses of the Koran by some combination of the two methods of flow on the body of Muslims at that time. The second stream is the hadîth experts and the rational. Seeing the importance of the interpretation of al-Shâfi?î, Islamic scholars vying to compile the results of the interpretation of al-Shâfi?î spread sporadically in his works, so comes the book Ahkâm al-Qur?ân li al-Imâm al-Shâfi?î created by Bayhaqî, Tafsîr al-Imâm al-Shâfi?î created by al-Shaurî, and the Tafsîr al-Imâm al-Shâfi?î created by al-Farran. This paper will explore the history of the Tafsîr al-Shâfi?î, al-Shâfi?î?s method of interpreting the Koran, and the characteristic that distinguishes it from the others commentators.